Mindfulness and acceptance-based training for elite adolescent athletes: a mixed-method exploratory study - Su, N.; Si, G.; Liang, W.; Bu, D.; Jiang, X. (Frontiers in Psychology, 2024)
Objectives This study aimed to examine the effectiveness of a specifically designed mindfulness-acceptance-insight-commitment (MAIC) training program on relevant psychological factors (i.e., mindfulness, acceptance, performance-related satisfaction) as well as sport training performance for elite adolescent athletes from Hong Kong. And it also aimed to explore the athletes` real experiences (i.e., receptiveness and perceptions) of completing the MAIC program.